Obituary of Harvey Lincoff - Kreissig, Ingrid (British journal of ophthalmology, 2018)
Harvey Alan Lincoff, MD, Professor of Ophthalmology, the Newhouse Clinical Scholar and the former Director of Retinal Research of the New York Presbyterian Hospital-Weill Cornell Medical Center, was a giant in the field of Retina and a highly estimated researcher, teacher and clinician. His patients loved him. - - He was born 22 August 1920 in Pittsburgh and passed away 25 November 2017 at the age of 97 when being at home in New York together with me, that is, Ingrid Kreissig. With me he sustained during 48 years a legendary transatlantic life partnership with ongoing impressive scientific and clinical creativity; we were soul mates, intellectual partners and always enjoyed each other’s company. - - Harvey Lincoff got a Heed Fellowship to go to Boston to study neuro-ophthalmology with David Cogan. While there, he took Edward Norton’s suggestion to meet up with the Schepens group. There was great enthusiasm in the retina department, and he began to spend more time with them and so became fascinated with the problems of retina and, subsequently, entered it as a full-time occupation. He developed a Retinal Detachment Service at the New York Hospital. The operation for detachment was then modelled on the Boston technique, which was largely encircling with drainage. - - In 1954, he was sent to Hans Karl Mueller in Bonn to evaluate their photocoagulation technique, which had been developed by Gerd Meyer-Schwickerath. Before leaving New York, Edward Norton asked him to look in on Ernst Custodis in Düsseldorf who claimed he was not draining subretinal fluid. In Bonn, he quickly appreciated the photocoagulator and bought one for New York. Then he went to Düsseldorf, of course, by …